Los juegos organizados en el desarrollo del lenguaje oral de los niños del nivel 1 paralelo “D” de la Unidad Educativa “Miguel Ángel León Pontón” de la ciudad de Riobamba, provincia de Chimborazo, periodo lectivo 2015-2016 - Rivera Carrasco, Anita Lucia (2017)
This work is the result of a project that was developed on organized games in the Oral Language Development in Children of the Level 1, parallel "D" of the Educational Unit "Miguel Angel León Pontón" from the City of Riobamba, Province of Chimborazo, which the main objective is to contribute with ludic activities that will help improve the Oral Language, for which similar researches were reviewed, obtaining references and databases to develop a comprehensive and well-supported work. The theoretical, scientific, methodological foundations are the main basis for developing this research, with a theoretical framework that is easy to understand and help the understanding of the raised issue. This research has demonstrated that meets their variables when the operationalization will be done. The research design was not experimental because the variables were not manipulated, the type of research was descriptive and of field and its level were descriptive, all this was done through the Observation Technique using as data collection one directed Observation Form aimed to 30 children. In the data interpretation, it shows that the highest percentages of children are not able to use the game theory Arranged as a tool to improve their oral language. In addition, it was concluded that the language of some children to enter the level 1 Initial education is scarce, no fluency and clarity but thanks to organized games children are motivated, constantly talk and are improving their language.